Corrosion study on steel sheets for car bodies - 458220 Mahyeaalagan Kanniah (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Mechanical Engineering (Materials) - Universiti Teknologi Malaysia, 2003